Enhancing Sustainability of Women-Led Rural Tourism MSMEs through Foreign Language Education, Digital Literacy, and Learning Agility - Togatorop, Firinta; Saragih, Doris Yolanda; Simarmata, Hengki Mangiring Parulian (Jurnal Ilmiah Global Education, 2025)
This study explores the influence of foreign language proficiency, digital literacy, and learning agility on the sustainability of women-led MSMEs in rural tourism, with digital literacy as a mediator and learning agility as a moderator. Guided by the Theory of Planned Behavior, Social Cognitive Theory, and Human Capital Theory, a quantitative explanatory design was employed using PLS-SEM on data from 300 women entrepreneurs in Samosir, Indonesia. Findings indicate that foreign language proficiency does not directly predict sustainability (β = 0.082; p = 0.080) but has a strong indirect effect via digital literacy (β = 0.393; p < 0.001). Language skills act as enablers rather than stand-alone drivers. Foreign language significantly enhances digital literacy (β = 0.837; p < 0.001), which in turn strongly predicts MSME sustainability (β = 0.469; p < 0.001). Learning agility also directly contributes (β = 0.414; p < 0.001) but does not moderate the language-sustainability link (β = −0.011; p = 0.238). The study advances theory by identifying digital literacy as a mediator and learning agility as an independent enabler. Practically, it recommends integrated, culturally grounded training. The primary limitation is its single-regional focus, suggesting future cross-regional, longitudinal, and conditional modeling.